The Impact of Integration of National Fitness and Healthy Elderly Care on the Psychological Status of the Elderly from the Perspective of Healthy China - Zhangbo Xiao; Shiyu Li; Chang Sun; Jiabing Zhang; Yanxia Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to address the health and elderly care issues brought about by the current aging population in China, research conducted to explore the impact of integration of national fitness and healthy elderly care on the psychological status of the elderly from the perspective of healthy china. Total 1900 questionnaires were distributed among elderly people in fitness. Used quantitative research approach and cross sectional research design. The SPSS software results indicates that frequency of urban elderly people participating in fitness is significantly higher than that of rural elderly people, among them, the highest proportion is once a week, followed by twice a week, the number of elderly people who participate in fitness more than three times a week is higher than those who participate three times a week, people are 3.2% higher, and rural elderly people participate in fitness more frequently, as the number increases, the participation rate gradually decreases. Under the guidance of the current "Healthy China" strategy, there are three paths for the integration of national fitness and the health and elderly care industry, namely concept integration, industry integration, and service integration. This study results also contributed that integration of national fitness and healthy elderly care can positively impact the psychological status of the elderly, promoting overall well-being and quality of life in the context of Healthy China.